Assessing Future Purchase Intentions in E-Commerce: An Empirical Study on Digital Consumers - Rorlen Rorlen; Margarita Ekadjaja; Christiandinata Tjandra Bravo (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
The purpose of this study is to investigate the determinants of consumers' intention to make online purchases. With the advent of digitalization, consumer shopping behaviour has been altered and this trend has started to affect their decisions to buy products online. Purchase intention is a measure of the likelihood of making purchase decision after exposure to digital media. User experience, platform trust, quality of service, and the weight of promotions and offers should all be weighted in this decision. Moreover, the effect of social media and their content quality also influences the customer loyalty and repurchase intention. The method in this paper uses a quantitative method approach by employing the PLS-SEM (Partial Least Squares Structural Equation Modeling) which uses SmartPLS. 14 Analysis of Results The results indicate that IBS exert significant influence on ABS as well as it does on FPI. In addition, CBF and IQS also affect purchase intention in the future mediated by IBS. Such results also indicate a need to increase consumer involvement when using e-commerce platform, particularly with social media to enrich consumers' relationships and increase sales conversions.